2020
DOI: 10.3354/ame01944
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and nutrient dynamics in mangrove, reef, and seagrass waters over tidal and diurnal time scales

Abstract: In coral reefs and adjacent seagrass meadow and mangrove environments, short temporal scales (i.e. tidal, diurnal) may have important influences on ecosystem processes and community structure, but these scales are rarely investigated. This study examines how tidal and diurnal forcings influence pelagic microorganisms and nutrient dynamics in 3 important and adjacent coastal biomes: mangroves, coral reefs, and seagrass meadows. We sampled for microbial (Bacteria and Archaea) community composition, cell abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 80 publications
3
22
0
1
Order By: Relevance
“…This resulted in the higher growth rates and significant reductions in FALS and fluorescence values recorded during post-sunset incubations (Table 1, Supp tables 3-4). For Prochlorococcus, the high division rates early in the evening resulted in higher cell abundance during the pre-sunrise incubation period, similar to diel patterns of cyanobacterial cell abundance observed across reef sites in the U.S. Virgin Islands (8,9). However, significant reductions in Prochlorococcus cell abundance due to predation by all three corals only occurs during the post-sunset incubation period, suggesting that predation is not driven by prey availability alone (Fig 4a-c).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This resulted in the higher growth rates and significant reductions in FALS and fluorescence values recorded during post-sunset incubations (Table 1, Supp tables 3-4). For Prochlorococcus, the high division rates early in the evening resulted in higher cell abundance during the pre-sunrise incubation period, similar to diel patterns of cyanobacterial cell abundance observed across reef sites in the U.S. Virgin Islands (8,9). However, significant reductions in Prochlorococcus cell abundance due to predation by all three corals only occurs during the post-sunset incubation period, suggesting that predation is not driven by prey availability alone (Fig 4a-c).…”
Section: Discussionsupporting
confidence: 61%
“…The microbial communities found in the water column surrounding and overlying coral reef systems are largely comprised of small phytoplankton such as picoeukaryotes, Prochlorococcus, Synechococcus, and heterotrophic bacteria (6)(7)(8)(9)(10). Reductions in particulate organic material (POM), as measured by carbon isotope ratios and carbon to nitrogen ratios, suggest that water column phytoplankton concentrations decrease across the reef crest in fringing reef systems (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, the picophytoplankton, Synechococcus and picoeukaryotes showed significant population growth during daytime (31.5  9.1 and 15.0  7.8 % cells mL -1 h -1 , respectively), but a low mortality rate during the dark incubations (2.4  0.8 and 5.3  2.8 % cells mL -1 h -1 , respectively). My observations of autotrophic picoplankton confirm the findings of Becker et al (2020), who also observed variability in these groups related to diurnal cycles in seagrass beds. However, while Becker et al (2020) found heterotrophic bacteria had a consistent abundance throughout the day (24 h) at their study sites, I found that the abundance of heterotrophic bacteria at my studied seagrass beds showed variation related to diurnal cycles.…”
Section: Picoplankton In the Seagrass Meadowsupporting
confidence: 88%
“…Even though they are located within the same bay, Donkey Bight and West Lameshur differ in coral cover [30]. Additionally, a mangrove swamp empties out near West Lameshur site, and therefore water quality parameters and reef communities are likely to vary among our sites [53], leading to differences in sh microbial consortia. In fact, several studies have shown that sh skin microbiota respond to changes in the physicochemical composition of the water [11,13].…”
Section: Goby Cleaning Activity Impacts Skin Microbial Diversitymentioning
confidence: 99%